Active Ageing Level and Time Use of Elderly Persons in a Thai Suburban Community - Autchariya Punyakaew; Suchitporn Lersilp; Supawadee Putthinoi (Occupational Therapy International)
Elderly populations are growing rapidly worldwide, thus enhancing an increasing need for their independent health care, productivity, and most importantly, balance of occupations. This research is aimed at investigating the active ageing levels and time use patterns of an elderly population attending the Community Elderly School in a suburban village of northern Thailand. These participants comprised 140 persons aged 60 years and older and were without cognitive deficits, based on the Mini-Mental State Examination. Active ageing levels and time use patterns were collected by following an interview-based questionnaire. The results showed that the level of active ageing was moderate (mean active ageing index (AAI) was 0.79). All of the participants used their time in varied activities, including the seven categories: basic activities of daily living, instrumental activities of daily living, rest and sleep, education, work, leisure, and social participation. Furthermore, they spent most of their time resting and sleeping.